2014
DOI: 10.1164/rccm.201307-1339oc
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea Syndrome Affects Liver Histology and Inflammatory Cell Activation in Pediatric Nonalcoholic Fatty Liver Disease, Regardless of Obesity/Insulin Resistance

Abstract: In pediatric NAFLD, OSAS is associated with biochemical, immunohistochemical, and histological features of NASH and fibrosis. The impact of hypoxemia correction on liver disease severity warrants evaluation in future trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 50 publications
7
85
1
2
Order By: Relevance
“…Eighty-one consecutive children with an ultrasonographic diagnosis of NAFLD, persistently (≥6 months) elevated serum aminotransferases and symptoms/signs suggestive of sleep apnoea,8 were prospectively seen and offered liver biopsy and polysomnography (PSG) as part of the experimental protocol, designed to evaluate the relationship of sleep disturbance with liver disease 1 8…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighty-one consecutive children with an ultrasonographic diagnosis of NAFLD, persistently (≥6 months) elevated serum aminotransferases and symptoms/signs suggestive of sleep apnoea,8 were prospectively seen and offered liver biopsy and polysomnography (PSG) as part of the experimental protocol, designed to evaluate the relationship of sleep disturbance with liver disease 1 8…”
Section: Methodsmentioning
confidence: 99%
“…Besides being an emerging cardiometabolic risk factor, OSAS has been recently connected to the presence and severity of liver disease in paediatric NAFLD, independently of whole-body/abdominal obesity, insulin resistance and metabolic syndrome (MS),8 9 but the mechanism(s) connecting OSAS to liver injury are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The same year Nobili et al confirmed similar incidence and the presence and severity of OSAS associated with the presence of NASH significant fibrosis, and NAFLD activity score independently of body mass index, abdominal adiposity, metabolic syndrome, and insulin resistance. This relationship held also in non-obese children with NAFLD and the duration of hemoglobin desaturation correlated with increased intrahepatic leukocytes and activated macrophages/Kupffer cells and with circulating markers of hepatocyte apoptosis and fibrogenesis [15]. The association OSA-NASH severity finally was found to correlate with increased endotoxemia coupled with impaired gut barrier function, leading to increased TLR-4-mediated hepatic susceptibility to endotoxemia [16], in keeping with the concept that gut microbiota plays a role in the development of hepatic steatosis and its progression to NASH [17].…”
Section: This Issue Ofmentioning
confidence: 71%
“…One of the worrisome consequences of obesity is the appearance of nonalcoholic fatty liver disease (NAFLD) and steatohepatitis (NASH), whereby a two-hit hypothesis, in which obesity constitutes one of the two hits, has been proposed (38). As a corollary to the significant adverse interactions between obesity and OSA, Nobili and colleagues prospectively evaluated sleep patterns among 65 of 66 consecutive obese children with abnormally elevated alanine aminotransferase (ALT) and NAFLD, a frequent occurrence in obese children with OSA, and performed a diagnostic liver biopsy for suspected NASH (39). In their cohort, 60% of children with NAFLD had concurrent OSA, and the prevalence of OSA in children with NASH was higher than in those without biopsy evidence of NASH.…”
Section: Pediatric Sleep Apneamentioning
confidence: 99%